Memberdayakan Anak Autis Sebagai Amanah Tuhan : Kajian Psikologi Lintas Budaya dengan Metode Client Centered - Saliyo, Saliyo (Community Development: Jurnal Pengembangan Masyarakat Islam, 2019)
This article was written aims to determine the proper empower method in children with autism. A surrogate child of God. Every child was born nothing is the same. No child is born with perfect physically, mentally. The other hand also children born to experience abnormality or disability. Whatever the situation of children who are born in the world, parents are obliged to maintain and empower. The goal as the provision of the future life of the child as an adult. Abnormality across studies in cross-cultural psychology studies. There is a difference of meaning in a place or state defines the abnormality. The basis of the difference gives meaning to the abnormality is due to cultural background. One part of abnormality or disability is a child with autism. An autistic child have outstanding advantages. Among these advantages is his intelligence. The other hand of autistic children also who experienced below-average intelligence. To achieve the a happy life of autistic children need education. One method is right for empowering children with autism are client centered method.